Thermal conductivity measurements of macroscopic frozen salt ice analogues of Jovian icy moons in support of the planned JUICE mission. Issue 3 (13th December 2021) - González Díaz, C; Aparicio Secanellas, S; Muñoz Caro, G M; Anaya Velayos, J J; Carrascosa, H; Hernández, M G; Muñoz-Iglesias, V; Marcos-Fernández, Á; Prieto-Ballesteros, O; Witasse, O; Lorente, R; Altobelli, N
ABSTRACT: The study of thermal properties of frozen salt solutions representative of ice layers in Jovian moons is crucial to support the JUpiter ICy moons Explorer (JUICE) (ESA) and Europa Clipper (NASA) missions, which will be launched in the upcoming years to make detailed observations of the giant gaseous planet Jupiter and three of its largest moons (Ganymede, Europa, and Callisto), due to the scarcity of experimental measurements. Therefore, we have conducted a set of experiments to measure and study the thermal conductivity of macroscopic frozen salt solutions of particular interest in these regions, including sodium chloride (NaCl), magnesium sulphate (MgSO4 ), sodium sulphate (Na2 SO4 ), and magnesium chloride (MgCl2 ). Measurements were performed at atmospheric pressure and temperatures from 0 to −70 °C in a climatic chamber. Temperature and calorimetry were measured during the course of the experiments. An interesting side effect of these measurements is that they served to spot phase changes in the frozen salt solutions, even for very low salt concentrations. A small sample of the liquid salt-water solution was set aside for the calorimetry measurements. These experiments and the measurements of thermal conductivity and calorimetry will be valuable to constrain the chemical composition, physical state, and temperature of the icy crusts of Ganymede, Europa, and Callisto.